MH tops list in North Carolina's action plan for school safety (Mental Health Weekly, 2021)
While additional security cameras and enhanced doors are vital to keeping students safe while on campus, state leaders stress mental health guidance should now be at the top of the list to make students safer while they attend school, Fox 8 News reported. On Aug. 2, state leaders and law enforcement held a School Safety Summit on the campus of the University of North Carolina Greensboro to detail what a school safety committee found after it studied North Carolina K–12 schools over three years. The committee was formed in the wake of the 2018 shooting in Parkland, Florida, where 17 students were killed and another 17 were injured. A study of 3,000 students found that nearly 19% had contemplated suicide, while nearly 10% admitted to having tried to take their own lives. Those numbers, while concerning, were also taken before the pandemic. Experts fear the numbers will become worse as COVID‐19 cases increase among younger individuals. The Action Plan for School Safety 2021–2026 suggests that districts hire more trained nurses and counselors who can identify when a student is struggling with mental health. The plan also suggests that teachers and school resource officers be trained to identify signs of mental health struggles as well.